Direct rapid prototyping of shape memory alloy with linear superelasticity via plasma arc deposition. (November 2018) - Lu, Bingwen; Cui, Xiufang; Feng, Xiangru; Dong, Meiling; Li, Yang; Cai, Zhaobing; Wang, Haidou; Jin, Guo
Abstract: Recently, additive manufacturing (AM) technology has drawn significant attention to fabricate shape memory alloys. In this study, plasma arc deposition (PAD), an AM technology, has been successfully applied to prepare the Ti51 Ni49 alloy directly and rapidly at the first time. The synthesized PAD Ti51 Ni49 alloy consisting of TiNi (B2), TiNi (B19′) and Ti2 Ni phase, exhibited primary TiNi columnar dendrites structure with a certain number of Ti2 Ni phases distributed in the interdendritic regions. The as-deposited Ti51 Ni49 alloy displayed a two-step phase transformation evidently (B2→ R → B19') during cooling process, and special linear superelasticity (up to 4.5%) with narrow hysteresis due to Ti2 Ni phase embedded in TiNi matrix phase. This work suggests that the PAD is an effective technology to directly and rapidly synthesize shape memory alloy. Highlights: Plasma arc deposition has been successfully applied to fabricate the shape memory alloy for the first time. The as-fabricated sample displays linear super-elasticity (up to 4.5%) with narrow hysteresis. Ti2 Ni phase intimated contact with the TiNi (B2) matrix phase is the origin of the unusual linear superelasticity.